PENGEMBANGAN SUMBER DAYA APARATUR PEREMPUAN - Sumarni Rumpot (AkMen JURNAL ILMIAH, 2010)
The women of developing appartur resource is to improve the ability of aparatur woman which in it include;cover the development of education and training. Development macroly represent an process is make-up of quality or ability manusiadan in environment an unit the work, development microly represent one of function from human resource management. That is: recruitment, select the, training and development. development of Resource appartur require to consider the factor eksternal and internal.